Die kenmerke van die gelowige en van die kerk by Calvyn, Institutio Christianae Religionis 1559, rv.1.7 en rv.1.9 - Pont, A. D. (Hervormde teologiese studies, 1993)
The marks of the faithful and of the church in Calvin’s Institutes, IV.1.7-IV.1.9 Calvin’s treatment of the marks of the church are very well known. Not so generally known is Calvin’s tre a tment of the marks of the faithful. W H Neuser has pointed out that the Institutes IV. 1.8 can be described as ‘an unnoticed part’. Calvin’s treatment of the marks of the faithful is discussed while taking Neuser’s opinion in consideration. It is shown that although the marks of the faithful are not as important as the marks of the church, they should play a very definitive part when discussing the organisation and building up of the congregation.